Educommunication as a strategy to face syphilis: an analysis of the open educational resources available at AVASUS - Valentim, Ricardo Alexsandro de Medeiros; Oliveira, Aliete Cunha; Dias, Aline de Pinho; Oliveira, Eloiza da Silva Gomes; Valentim, Janaína Luana Rodrigues da Silva; Moreira, José Antônio Maques; Coutinho, Karilany Dantas; Trindade, Sara Marisa da Graça Dias do Carmo; Bonfim , Marilyn Anderson Alves (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: Syphilis is a problem for the Brazilian Public Health. Therefore, the Brazilian Ministry of Health has been promoting actions to fight this disease; among them, the “No Syphilis Project” stands out, and develops open educational resources (OER), among several activities. Objective: To analyze the open educational resources available in the SUS (the Brazilian Unified Health System) Virtual Learning Environment, focused on syphilis. Methods: This qualitative study, based on epistemology in the field of phenomenology, is a content analysis operated with the meanings constructed to parts of a set of texts and the objects of its analysis were the teaching plans of 19 educational resources available at AVASUS, which dealt with the theme “Syphilis”. The analysis was organized into two unitss: The main purpose of the educational resource and Thematic focus of the educational resource. Results: The overlapping of clinical aspects of the disease to the detriment of socio-environmental aspects and the prevalence of informational objectives can be observed, with the exception of one resource that presented an objective that sought a more active action by the course participant. In the analysis unit 1 it was possible to identify the prevalence of objectives such as ’presenting’ or ’conveying’ content/information related to the disease. In the analysis unit 2 it was possible to identify the “classic” biomedical cycle of approaching a disease, focusing on diagnosis. Conclusion: The study contributed to the identification of gaps from the thematic and methodological point of view that can guide the planning for the construction of new educational resources.